Human Capital Investment: The Datai Sets a Risky Example (Journal of Business Management and Accounting, 2020)
Human capital investment is important for service firms that provide personalised services, for example,  luxury  hotels.  Hotels  in  Langkawi  claim  that  they  conduct continuous training. The extent of the training is just sufficient to fulfil the Ministry of Human Resources training requirements. Rarely do businesses spend above the minimum requirement. This is especially true in the hotel industry, an industry that many perceive as a stepping stone in building their careers. This makes it significant to conduct and in-depth interview with the master minds of The Datai Investing in People (DIP) training programme. The purpose of the interviews is to investigate how human capital investment is carried out in the hotel industry. Furthermore, the fact that covid-19 spreads around the world only a year after the “new” Datai reopens makes it seems riskier as it is very doubtful that the hotel will get the expected returns from its investment. The findings of this study may enhance understanding of human capital investment in the hotel industry as it provides in-depth explanation of how The Datai invests in its human capital. The finding will also bridge the gap between theory and practice as it enhances understanding of why many hotels choose to limit their human capital investment.  The Datai’s sacrifice makes it clear why it has remained as the employer of choice.